2015
DOI: 10.3892/ol.2015.2869
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of crocetin in human esophageal squamous cell carcinoma KYSE-150 cells

Abstract: Crocetin is the main pharmacologically-active component of saffron and has been considered as a promising candidate for cancer chemoprevention. The purpose of the present study was to investigate the anticancer effects of crocetin and the possible mechanisms of these properties in the esophageal squamous cell carcinoma cell line KYSE-150. The KYSE-150 cells were cultured in Dulbecco’s modified Eagle’s medium and incubated with 0, 12.5, 25, 50, 100 or 200 μmol/l crocetin for 48 h. Cell proliferation was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Saffron is a Chinese traditional herb, and Crocetin is the major constituent of saffron, which has recently found to have multiple pharmacological effects including anticancer [15][16][17]. However, the effects of Crocetin on asthma as well as the underlying mechanisms have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Saffron is a Chinese traditional herb, and Crocetin is the major constituent of saffron, which has recently found to have multiple pharmacological effects including anticancer [15][16][17]. However, the effects of Crocetin on asthma as well as the underlying mechanisms have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Increased incidence of esophageal cancer is due to obesity, smoking, consumption of hot beverages and red meat, increased alcohol intake and a decreased intake of fresh vegetables or fruit (22). The morbidity of squamous cell carcinoma is increasing in developing countries, particularly in China (23). According to the cancer stem cell theory, malignant tumors develop from a cancer stem cell, which has the capability of pluripotency and self-renewal (24).…”
Section: Discussionmentioning
confidence: 99%
“…It also has anticancer effects. Growing evidence has indicated that crocetin can inhibit the proliferation of cancer cells in vitro [16,17] and regress the growth and metastases of tumors in vivo [16,18]. Moreover, the in vivo and in vitro showed that crocetin has no cytotoxic effects on normal cells [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The cell proliferation was determined using MTT assay, as reported in our previous study [17]. To summarize briefly, cells were plated in 96 well plates at 6,000 cells/well.…”
Section: Mtt Assaymentioning
confidence: 99%